Intelligent computation offloading for educational virtual reality applications in smart campus using MoCell. (11th June 2022) - Liu, Peichen; Peng, Kai; Tao, Peng
Abstract: Nowadays, as the smart campus concept becomes a reality, virtual reality (VR) applications are being applied to connect students with the virtual teaching world via VR devices (VDs), enhancing learning efficiency. Nevertheless, VR applications are latency‐sensitive while VDs are subjected to shortcomings to handle many VR applications simultaneously. Fortunately, mobile edge computing (MEC) has been recognized as a promising solution that can bring abundant resources to VDs to relieve hardware limits. However, the computing resources of edge nodes in MEC are limited, and thus how to allocate resources effectively is critical. Meanwhile, some sensitive information of students collected by VD needs to be protected. In view of this, we investigate computation offloading for educational VR applications in MEC‐enabled smart campus. The aims of this issue are to optimize the motion‐to‐photon latency, energy consumption, and resource utilization while satisfying the privacy and security constraints. To this end, we propose a new multi‐objective optimization method using MoCell. Eventually, the experimental evaluations are designed to illustrate the effectiveness and superiority our proposed method.